Cadmium (Cd) Absorption and Phenol Content in Pogostemon Exposed to Heavy Metals - Elly Proklamasiningsih; Iman Budisantoso; Kamsinah Kamsinah (Journal of Tropical Life Science, 2018)
Patchouli (Pogostemon cablin Benth.) is an important plant used by industrial facilities to absorb cadmium (Cd) in polluted land. We performed an experiment using plant medium polluted with both Cd and lead (Pb) with added humic acid. The aims of this study were to 1) determine the effects of humic acid in growth medium contaminated with Cd and Pb on the absorption of Cd and phenol content in patchouli, and 2) determine the Cd tolerance level of the growth media. A completely randomized factorial design was used for the experiment with two factors. The heavy metals were a combination of pure PbNO3 and Cd (PC) with a ratio 1 : 1, and included five concentrations: PC0 (without PbNO3 and without Cd); PC1 (250 ppm PbNO3 + 250 ppm Cd); PC2 (500 ppm PbNO3 + 500 ppm Cd); PC3 (750 ppm PbNO3 + 750 ppm Cd); PC4 (1,000 ppm PbNO3 + 1,000 ppm Cd) and humic acid concentration (0; 6,000; 12,000; and 18,000 ppm). Each treatment was replicated three times. The parameters observed were plant biomass, Cd absorption, and phenol content. The application rate of humic acid to the plant medium containing heavy metals influenced the growth of patchouli, Cd absorption, and phenol content. An application rate of 12,000 ppm of humic acid reduced the toxicity of the heavy metals and increased the dry biomass and phenol content of patchouli.